ANALISIS PELUANG PENERBITAN OBLIGASI DAERAH SEBAGAI ALTERNATIF PEMBIAYAAN DAERAH - Dewi Okta; David Kaluge (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
Municipal bonds may be used as a source of regional funding.This study aims toanalyze the feasibility of issuing municipal bonds as an alternative source of financ-ing local infrastructure and analyze the strategies to be implemented by the govern-ment in the issuance of local bonds. Analysis tools used in this study were descriptivestatistics and SWOT analysis. The analysis showed that municipal bonds are an alter-native worth considering as a source of financing funding than other areas.Keywords: municipal bonds, the financing area, the SWOT.